Immoral memories : an autobiography - Eisenstein, Sergei M., (1898-1948); Marshall, Herbert (Boston : Houghton Mifflin, 1983)
The autobiography of pioneering Soviet Russian film director and film theorist Sergei Eisenstein, noted in particular for his silent films, 'Strike' (1924) and 'October' (1927).
Incluye referencias bibliograficas e indice.
Keywords: Eisenstein, Sergei M., ( -- 1898-1948); Autobiografías; Lengua inglesa